PENGARUH GAYA KOMUNIKASI ATASAN DAN PENGEMBANGAN KARIER TERHADAP MOTIVASI KERJA PEGAWAI INSTITUT AGAMA ISLAM NEGERI PADANGSIDIMPUAN - Hj. ZULHIMMA (Institut Agama Islam Negeri Padangsidimpuan, 2017)
This research is purposed to know the significant effect of communication style of the leaders and development of carrier to the employees’ work motivation in IAIN Padangsidimpuan. The population was all of the employees in IAIN Padangsidimpuan with 40 people as sample. It is a quantitative research in ex-post facto. The instrument was questionnaires by using Likert scale. The result shows that coefficient correlation between communication style and work motivation was 0.27, and the correlation is not significant because tcount= 1.72 ttable (38)(0,05)= 2.0252. Then, the coefficient correlation between carrier development and work motivation was positive 0.22, and the result of tcount was 1.39 ttable (33)(0,05). It means that no significant correlation between both variables. The last, the correlation between the variables simultaneously was 0.28, and it was also not significant, because Fcount =1.57, F(2,38)(0,05)= 3,25, and F (2,38)(0,01)= 5,21. It shows that Fcount dari Ftable (2,38)(0,01). It means that the correlation between style to lead and carrier development to work motivation was very weak or not significant.